2022
DOI: 10.3390/cancers14112622
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Investigation on p75ICD Expression in Laryngeal Squamous Cell Carcinoma

Abstract: We investigated the p75 Neurotrophin Receptor (p75NTR) expression and cleavage product p75NTR Intracellular Domain (p75ICD) as potential oncogenic and metastatic markers in human Laryngeal Squamous Cell Carcinoma (LSCC). p75NTR is highly expressed in Cancer Stem Cells (CSCs) of the laryngeal epithelia and it has been proposed as a marker for stemness, cell migration, and chemo-resistance in different squamous carcinomas. To investigate the clinical significance of p75NTR cleavage products in solid tumors, full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A detailed analysis of the sublocalization of ABCG2 immunoreactivity has not been described, although several papers mention the possible importance of intracellular localization of the protein. Several studies have observed membranous and nuclear expression of ABCG2 in malignant tumor cells, such as lung and laryngeal carcinomas and glioblastoma multiforme [ 67 , 68 , 69 ]. A possible novel role of ABCG2 within the nucleus as a transcriptional regulator involved in modulation of metastasis has been proposed in lung cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of the sublocalization of ABCG2 immunoreactivity has not been described, although several papers mention the possible importance of intracellular localization of the protein. Several studies have observed membranous and nuclear expression of ABCG2 in malignant tumor cells, such as lung and laryngeal carcinomas and glioblastoma multiforme [ 67 , 68 , 69 ]. A possible novel role of ABCG2 within the nucleus as a transcriptional regulator involved in modulation of metastasis has been proposed in lung cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several papers plasma membrane, as well as nuclear ABCG2 immunoreactivity was observed in cancer cells, namely lung cancer cells, laryngeal squamous cancer cells and glioblastoma multiforme cells. [39][40][41] A potential novel role for nuclear ABCG2 was proposed, as a transcription regulator participating in modulation of cancer metastasis in lung cancer cells. 40 In our specimen beside membrane and cytoplasm ABCG2 immunoreactivity we have also observed nuclear one (Figure 1D).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, detail analysis of ABCG2 sublocalization immunoreactivity was not described, although a few investigations have been reported. In several papers plasma membrane, as well as nuclear ABCG2 immunoreactivity was observed in cancer cells, namely lung cancer cells, laryngeal squamous cancer cells and glioblastoma multiforme cells 39–41 . A potential novel role for nuclear ABCG2 was proposed, as a transcription regulator participating in modulation of cancer metastasis in lung cancer cells 40 …”
Section: Discussionmentioning
confidence: 99%